ANALISIS KEMAMPUAN BERBICARA BAHASA INDONESIA ANAK USIA 4-5 TAHUN DI PAUD MARINGU KECAMATAN TERIAK - Sulasmi, Neni; Ali, Muhamad; Halida, Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract           This research is motivated by the fact that most children have not been able to speak Indonesian. Children are more likely to use the local language, namely Banyadu, even though the teacher uses Indonesian language. This study aims to determine the ability to speak Indonesian in children aged 4-5 years in PAUD Maringu Kec Teriak Bengkayang District. The method used in this research is qualitative method. Based on the results of a study on the analysis of Indonesian speaking ability, 4-5 years old children in PAUD Maringu, Teriak Subdistrict, Bengkayang Regency showed the results that most of the children were able to speak Indonesian because the teacher always motivated and improved children who had difficulty speaking and getting used to talking using Indonesian. Where the accuracy of speech in speaking Indonesian children aged 4-5 years some children are able to speak appropriately and are categorized as developing according to expectations. Accuracy in using question sentences in Indonesian children aged 4-5 years in PAUD Maringu can be said to develop according to expectations or develop very well. The fluency in expressing opinions in simple terms in Indonesian children aged 4-5 years in PAUD Maringu can already be said to develop according to expectations or develop very well. Keywords: Ability, Speaking